Fishermen Perspective and Dinamization toward Social Welfare Effort - Pranowo Pranowo; A Nururrochman Hidayatullah (Jurnal Penelitian Kesejahteraan Sosial, 2015)
This research means to describe fishermen perspective, dinamization, and aspiration toward social welfare effort in Tanjungbalai Municipality, North Sumatera Province. This research is done with qualitative method and analyzed through descriptive technique. Data resources are fishermen as informants united in Rumah Kerang, secondary data are from previousresearch literatures and books related to the research topic. Research location determined purposively based on the consideration that Tanjungbalai is strategic port. Data are gathered through interview and observation technique. The result shows that fishermen in Tanjungbalai depend on sea resources, namely fish and clam through cooperation system called Rumah Kerang that is expected to give welfare to the fishermen. Fishermen perspective toward social welfare effort is still based on religious power. It is recommended that government should arrange regulation on fish-catching zonation, use catching devices with environmental friendly, eradicat black levy and high-interest money lender toward fishermen. For small fishermen they should get guidance, law awareness, preserve sea echosystem, and empowerment through fasilitation, job diversification, and fish cultivication through netbox.